Impact of sports vision training on visuomotor skills and shooting performance in elite skeet shooters - Guo, Yuqiang; Yuan, Tinggang; Peng, Jian; Deng, Liwei; Chen, Chao (Frontiers in Human Neuroscience, 2024)
IntroductionVision serves as a critical channel for athletes to acquire information during competitions and constitutes a vital component of their competitive ability. Through scientifically designed sports visual training, specific visual skills can be enhanced, thereby assisting athletes in achieving optimal performance in competitive settings. This study aim to explore the visuomotor abilities and shooting performance of skeet shooters through Sports Vision Training (SVT).MethodsTwenty elite skeet shooters were recruited and randomly assigned to an experimental group (EXP, n = 10) and a control group (CON, n = 10). The EXP underwent 6-week of SVT on Senaptec Seneory Station, twice a week, while the CON completed an equivalent workload of target-tracking training.ResultVisuomotor skills testing showed significant improvements in Near- Far Quickness, Perception Span, and Eye-hand Coordination in the EXP (p < 0.05), with no changes in the CON. Comparative post-test results between the two groups showed significant differences in N/F Q, Target Capture, Perception Span, Eye-hand Coordination, and Go/ No Go (p < 0.05). In shooting performance indicators, EXP shooters showed a highly significant improvement in hit accuracy (p < 0.01), with a similar difference compared to the CON. Additionally, they exhibited a highly significant improvement in shotgun-mounting reaction time (p < 0.01). Kinematic indicators of shotgun movement during the firing process for shot 2 showed significant differences in peak velocity (p < 0.01), X-axis (p = 0.033) and Y-axis (p = 0.001) displacement.ConclusionSVT can enhance visuomotor abilities in skeet shooters and has a positive impact on their shooting technique. This is primarily manifested in shorter shotgun-mounting reaction time and improved efficiency in action at shot 2, effectively improving their shooting accuracy.